JURGEN HABERMAS DAN HERMENEUTIKA KRITIS (SEBUAH GERAKAN EVOLUSI SOSIAL) - Ulumuddin Ulumuddin (Hunafa: Jurnal Studia Islamika, 2006)
Jurgen Habermas was born in Germany on June 18, 1929. He is a very influential philosopher in contemporary era. He constructed his philosophical thoughts after he had involved in  Frankfurt School of Philosophy. Since 1960’s his thoughts on philosophy and social sciences had became more and more influential. He was a type of philosopher who was very critical to Marxism, not only to orthodox-Marxism but also to neo-Marxism.  He endeavored to adapt Marx’s heritages of thoughts to his time needs. This article will elaborate Habermas’s hermeneutics of critique. Kata Kunci: Jurgen Habermas, hermeneutika kritis, filsafat